Regional migration governance: contributions to a sustainable international migration architecture - Eva Dick; Anne Koch; Benjamin Schraven; Benjamin Etzold (Deutsches Institut für Entwicklungspolitik (DIE), 2018)
The global migration governance is in a period of transition. There are two main reasons for this: First, the division between an international refugee regime based on the 1951 Geneva Convention on Refugees and a (labour) migration regime is problematic in light of `mixed' migratory flows. Second, the current global migration architecture is characterised by institutional fragmentation and a lack of normative standards. The Global Compact for Migration and the Global Compact on Refugees currently being negotiated are intended to address these shortcomings. Among the crucial questions to be addressed is the role of regional cooperation in a future global migration architecture. This is because the majority of cross-border migration and displacement takes place within regional spaces. Regional cooperation on migration currently occurs in three formats, all of which focus on different issue areas: 1) Migration-related activities of regional organisations (ECOWAS, IGAD, for instance); 2) regional consultative processes (RCPs) and 3) inter-regional cooperation processes (such as Khartoum and Rabat Processes). Experiences from Africa suggest: Groundbreaking norms, for example for the free movement of persons or on refugee rights have been developed on the regional level. This is not least due to some advantages of regional migration governance over global formats. Joint interests tend to be identified more easily, distinct regional features can be better addressed and forging common ground in the formulation of a coherent and developmental migration policy is generally not as difficult. However, in Africa as yet the implementation of regional norms has been deficient. Moreover, the agendas of inter-regional cooperation formats are often strongly influenced by economic and security- interests of Western donors. In this context, the promotion of the protection of refugees' and migrants' rights tends to be neglected. Also regional migration interests risk to be undermined. Therefore, additional to regional migration policies, it is necessary to establish binding, universal standards under international law as regards the rights and protection of refugees and migrants. At the same time, the regional level ought to be strengthened. It can provide important impulses for expanding standards of protection and implementing orderly, safe, regular and responsible migration. The international community has to take this into account in the negotiation of the two global Compacts. The con-tributions of German and European development policy ought to focus on the following: Building capacities: Regional organisations ought to be supported financially and technically in all areas of migration, not only in security-relevant aspects. Fostering interaction: Regular exchange among regional organisations and global actors as well as civil society actors should be strengthened. Increasing influence: The weight of regional organisations in global policy processes and in the review and follow-up of the Compacts must be enhanced. __________________ Anne Koch: Research division “Global Issues”, Stiftung Wissenschaft und Politik (SWP) Benjamin Etzold: Bonn International Center for Conversion (BICC)
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Regionale + globale + transnationale Governance